MENINGKATKAN KEAMANAN KENDARAAN BERMOTOR DENGAN MEMBUAT ALAT FINGER PRINT - M. Adi Rahman; Hamsir Hamsir; Lukman Lukman (Universitas Lambung Mangkurat, 2019)
One of the problems faced by motor vehicle users is the frequent theft and loss of motorbikes. The purpose of the study was to design a finger with the aim of increasing the safety of motorvehicles. The method use in the research is the research method used with the case study approach method which is the innovation of making motorcycle vehicle safety devices that will function as a log out so that motorized vehicles cannot run if they do not use the ignition key of the motor vehicle owner. The expect results of this study are the availability of motor vehicles safety devices so that the potential loss of motorvehicles can be reduce. The results of this study are expect to be useful for the benefit of many people and can be develoveas industrial innovation